The impact of technology parks services on the high technology industry: A case study on Kulim Hi-Tech Park - Abidin, Rahimi (2013)
The emergence of technology parks in Malaysia typically generates the expectations that they will contribute significantly to the industrialization.Accordingly, there is increasing number of research conducted on technology parks performance.However, there is still uncertainty about whether technology parks are achieving their goals or not and exactly what their impact is on their tenants. This paper attempts to contribute in understanding this issue by focusing specifically on the technology park services.A case study on one of well established technology parks in Malaysia that is Kulim Hi-Tech Park (KHTP) has been conducted.After a series of interviews with the administrator and review on literature, nine evaluation criteria were identified and used to observe the impact of technology park services on the industrial tenants of the technology park.From a survey on the industrial tenants in KHTP it is found that the technology park has all the nine evaluated criteria.However, these criteria have different categories of impact on the tenants. It can be concluded that the there are still more room to improve in ensuring the competitiveness of the technology park. The results have significant implications for the administrator of the KHTP.